Auswirkungen intrastromaler Presbyopiebehandlung mittels Femtosekundenlaser (INTRACOR) auf die mesopische Kontrastsensitivität - Fitting, Anna; Menassa, Nardine; Auffarth, Gerd U.; Holzer, Mike P. (Der Ophthalmologe, 2012)
BackgroundThe aim of this study was to examine the mesopic contrast sensitivity (CS) and glare sensitivity following intrastromal femtosecond laser correction of presbyopia (INTRACOR).Patients and methodsIn this study 25 patients with slight hyperopia and presbyopia underwent femtosecond laser correction in the non-dominant eye. Mesotest II measurements (OCULUS Optikgeräte, Wetzlar, Germany) were performed with and without glare at each of four different contrast levels preoperatively as well as 3, 6, 12, 18 and 24 months postoperatively. Data were compared using the Wilcoxon-test with a level of significance of p < 0.05.ResultsAfter 24 months the median CS decreased from 1:2 to 1:2.7 without glare and from 1:23 to 0 with glare. Of all patients 36% showed loss in CS without and 52% with glare and CS did not show any statistically significant differences between the treated and the untreated fellow eyes after 12 and 24 months. Overall 9 out of 18 monocular treated patients showed no binocular night driving ability according to the recommendations of the German Society of Ophthalmology (DOG) and the Professional Association of German Ophthalmologists (BVA) 24 months following INTRACOR.ConclusionsINTRACOR can lead to a slight reduction of mesopic contrast sensitivity and an increase of glare sensitivity. Possible consequences on night driving ability should be discussed with the patients prior to treatment.